(untitled) (Comillas Journal of International Relations, 2016)
In this extract from his new book Churchill’s Legacy: Two Speeches to Save the World (Watson, 2016), Lord Watson of Richmond draws on his own experience of post war British politics, as a television presenter and media commentator and then as a Liberal Peer and Chairman of the English-Speaking Union, to analyse the significance of Churchill’s Zurich speech of 19 September 1946. He argues that, building on Churchill’s earlier speech at Fulton, Missouri, it helped change the perceptions of the West and alter their response to the emerging Cold War and the future of Europe.